2017
DOI: 10.1007/s11255-017-1525-y
|View full text |Cite
|
Sign up to set email alerts
|

Validation of 3D volumetric-based renal function prediction calculator for nephron sparing surgery

Abstract: Objective To evaluate a recently published volume-based renal function prediction calculator intended to be used in small renal mass surgical counseling. Methods Retrospective data collection included 3-dimensional calculation of renal mass and parenchyma of patients who have undergone extirpative therapy. The predicted glomerular filtration rate (GFR) was calculated using the online calculator. The predicted GFR was compared with the actual 6-month GFR. The Pearson correlation coefficient, paired T-test and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Prognostic factors including anatomical, histological, clinical and molecular factors were found to be facilitators to decision making in kidney cancer in this review. 12–32 This is similar to the findings reported in Campi et al’s SR: they identified most decisions are based on tumor related factors and renal mass growth was the most influential trigger. 54 This was consistent with our findings, where prognostic factors were identified as facilitators to clinical decision making.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Prognostic factors including anatomical, histological, clinical and molecular factors were found to be facilitators to decision making in kidney cancer in this review. 12–32 This is similar to the findings reported in Campi et al’s SR: they identified most decisions are based on tumor related factors and renal mass growth was the most influential trigger. 54 This was consistent with our findings, where prognostic factors were identified as facilitators to clinical decision making.…”
Section: Discussionsupporting
confidence: 87%
“…Eleven papers described predictive tools to support decision making. 12,13,15,17,20,22,27,33,35,44,48 The RENAL (radius, exophytic/endophytic, nearness of tumor to collecting system, anterior/posterior, location relative to polar line) nephrectomy score was used to help overcome selection bias, 31 assist surgeons in preoperative decision making 48 and correlate with tumor histology and grade. 35,44 Similarly, the PADUA score was reported to support the process of decision making by identifying the tumor complexity.…”
Section: Patient Demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative renal function and chronic kidney disease remain a concern in the surgical management of renal masses, as they has been related to an increased risk of hospitalization, cardiovascular morbidity and death [33,58]. Few papers [31][32][33]60] have focused directly on the relationship between postoperative renal function and resected cortex margin volume, calculated by a 3D reconstruction technique based on the resected specimen, to determine the predictors of renal function after robot-assisted partial nephrectomy. Meyer et al [32] found that using accurate 3D volumetric analysis, ischemia time, tumor size and endophytic/exophytic properties of a localized renal mass were the most important determiners of renal parenchymal volume loss.…”
Section: Presurgical Stimulation and Intra-operative Navigation Mappingmentioning
confidence: 99%
“…The creation of a multi‐institutional open‐source dataset of annotated renal CT scans would pave the way for increased research and progress towards automatic, reliable and quantitative image analysis tools for kidney cancer. In particular, research on 3D nephrometric scoring , image‐based volumetry (segmentation) and tracking of tumours to assess the response of therapy , and CT volumetry to predict 6‐month postoperative estimated GFR could be developed into fully automatic and robust software that finds its way into clinical practice.…”
mentioning
confidence: 99%